2004
DOI: 10.1063/1.1791031
|View full text |Cite
|
Sign up to set email alerts
|

Complete structural and magnetic characterization of biological radicals in solution by an integrated quantum mechanical approach: Glycyl radical as a case study

Abstract: An integrated quantum mechanical approach for the structural and magnetic characterization of flexible free radicals in solution has been applied to a model of the glycyl radical engaged in peptidic chains. The hyperfine couplings computed using hybrid density functionals and purposely tailored basis sets are in good agreement with experiment when vibrational averaging effects from low frequency motions and solvent effects (both direct H bonding and bulk) are taken into the proper account. The g tensor shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 65 publications
4
70
0
Order By: Relevance
“…The approach includes not only the dominant second-order spin-orbit/orbital-Zeeman terms but also the relativistic mass correction (RMC) and the one-electron part of the gauge correction (GC) terms. 43,44 We note in passing that the out-of-plane vibration of H R has been previously found to affect non-negligibly the C R and H R hyperfine couplings but not the g-tensor of model systems, 23 and we thus consider static computations adequate.…”
Section: Computational Detailsmentioning
confidence: 96%
See 1 more Smart Citation
“…The approach includes not only the dominant second-order spin-orbit/orbital-Zeeman terms but also the relativistic mass correction (RMC) and the one-electron part of the gauge correction (GC) terms. 43,44 We note in passing that the out-of-plane vibration of H R has been previously found to affect non-negligibly the C R and H R hyperfine couplings but not the g-tensor of model systems, 23 and we thus consider static computations adequate.…”
Section: Computational Detailsmentioning
confidence: 96%
“…Himo et al have investigated the local structure of the protein-bound radical and suggested a nonplanar structure of the glycyl radical in bacteriophage T 4 anaerobic ribonucleotide reductase (ARNR) to explain its somewhat larger 13 C R hyperfine coupling (HFC) (A zz ) compared to the PFL and E. coli ARNR enzymes. 24 During the course of the present work, two DFT studies were reported that dealt also with the g-tensor of N-formylglycyl 23,25 forms of the glycyl radical. In both cases, the emphasis was on the validation of a given computational protocol, using semiempirical spin-orbit (SO) operators.…”
Section: Introductionmentioning
confidence: 98%
“…Despite of the fully theoretical approach used to hybridize it, this functional is comparable in accuracy to B3LYP, when not better for specific properties. [37][38][39][40] . Figure 1 shows the impact of the exact-exchange fraction on the accuracy for the atomization energy of the G2-148 dataset.…”
Section: Theorymentioning
confidence: 99%
“…Recently, density functional theory (DFT) calculations, together with the inclusion of explicit solvent and ab initio calculation of fast librational motions, [22,23] have shown to be highly predictive for both the electron g tensor [24][25][26][27][28][29] and the nucleus-electron hyperfine coupling tensors A [30][31][32][33][34][35][36][37][38][39]. Not only the principal values of the tensors are well reproduced but also their orientation in the molecule.…”
Section: Quantum Mechanical Propertiesmentioning
confidence: 98%